Case Report: Hybrid approach as a Rescue Treatment in a patient with vascular Ehlers–Danlos Syndrome - Park, Suehyun; Hwang, Deokbi; Yun, Woo-Sung; Kim, Hyung-Kee; Huh, Seung (Frontiers in Surgery, 2023)
Vascular Ehlers-Danlos Syndrome (vEDS) is a rare connective tissue disorder associated with COL3A1 gene mutation encoding type III collagen. Given the possible fatal prognosis if not treated timely, it is important to suspect and diagnose as soon as possible. Despite advances in endovascular technique, access point complications remain a serious challenge in patients with vEDS. Here, we describe a 30-year-old male patient who was diagnosed with vEDS after consecutive events of bilateral iliac vessels at an interval of 3 months: (1) spontaneous dissecting aneurysm of right iliac artery and (2) arteriovenous fistula between left internal iliac artery (IIA) and left common iliac vein. This patient was treated with iliac stent-grafts and overlapping femoral interposition graft (Dacron) in the 1 st operation and access artery repair with surgical dissection after coil embolization of IIA and stent-graft insertion into left common to external iliac arteries in the 2 nd operation. The patient has been treated with betablockers and anticoagulants for the management of vEDS and postoperative deep vein thrombosis, respectively. The stent-grafts in both iliac arteries and the access sites have been well-tolerated without any adverse effects for 14 months following the 2 nd operation. In conclusion, given the vascular fragility and the potential for future events, additional vascular manipulation should be avoided unless it is in a life-threatening condition. In particular, meticulous hybrid interventions can be effective treatments.